Optimalisasi Penyuluhan Sat Binmas dalam Mencegah Pencurian Kendaraan Bermotor Roda Dua di Wilayah Hukum Polres Purwakarta - Dani Hayqal (Indonesian Journal of Police Studies, 2021)
This research is motivated by the high number of motor vehicle theft cases in the Purwakarta district police jurisdiction which has been increasing in the last 2 years. The National Police of the Republic of Indonesia makes pre-emptive and preventive efforts to prevent the occurrence of criminal acts of vehicle thief, especially two-wheeled vehicles, one of which is through counseling through Binmas units. Therefore, research is carried out that aims to find out the description of counseling by the Binmas Unit in order to prevent the criminal act of stealing two-wheeled motor vehicles, the factors that influence and efforts to optimize counseling by the Binmas Unit in the prevention of criminal acts of two-wheeled vehicle thief in the jurisdiction Purwakarta Police Station. Literature review consists of research literature using references from the previous 2 Thesis. For conceptual literature use management theory and communication theory. The concept used is the concept of counseling, the concept of optimization, the concept of crime and fraud, the concept of counseling. The study was conducted with a qualitative approach. Data sources include primary data, secondary data and tertiary data. Data collection techniques used were through interviews and observations. The analysis used data reduction, data presentation and conclusion drawing. The results of the study found that the implementation of counseling conducted by the Purwakarta Police Sub-dept was still not optimal and there were influencing factors. The inhibiting factor of counseling by Binmas Unit is that personnel are still deemed lacking in quality and quantity, the implementation of counseling is also not optimal. Efforts are being made to optimize counseling by Binmas Unit is to overcome the factors that hamper the counseling activities by Binmas Unit, using crime prevention theories to find the right material and targets for counseling. Suggestions from researchers to optimize counseling by Binmas Unit (1) improve the quality of personnel by providing training or vocational education and development education and can be trained by function leaders (2) innovating in conducting counseling (3) creating an organizing team (4) creating new programs which can improve extension services (5) provide facilities and infrastructure for extension services.